2010
DOI: 10.1029/2009jb006865
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fracture systems using precise array locations of earthquake multiplets: An example at Deception Island volcano, Antarctica

Abstract: [1] Volcano-tectonic earthquakes are common seismic events in active volcanic areas. The stress produced by volcanic processes is released through fracturing of the shallow crust. Very often, these earthquakes occur in multiplets with similar waveforms, a fact which indicates common source characteristics. In this work, we introduce a method that uses array techniques to calculate precise relative locations of earthquake multiplets. We use the relative slowness estimate method to determine accurately the appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 94 publications
(134 reference statements)
0
27
0
Order By: Relevance
“…The study of the seismic activity of the volcano is probably the most active and productive research line, as reported by Tejedo et al (2014). There are many results that help us better understand the dynamic and volcanological framework of the area, such as Vila et al (1992), , Ibáñez et al (1997Ibáñez et al ( , 2000Ibáñez et al ( , 2003, Saccorotti et al (2001), Martinez-Arevalo et al (2003), Benitez et al (2007), Carmona et al (2010Carmona et al ( , 2012Carmona et al ( , 2014, and García-Yeguas et al (2010). One of the objectives of these seismic studies is to provide 2D or 3D structure of the area, by using active or passive data as has been done by Ben-Zvi et al (2009), Zandomeneghi et al (2009), and Prudencio et al (2013).…”
Section: Introductionmentioning
confidence: 92%
“…The study of the seismic activity of the volcano is probably the most active and productive research line, as reported by Tejedo et al (2014). There are many results that help us better understand the dynamic and volcanological framework of the area, such as Vila et al (1992), , Ibáñez et al (1997Ibáñez et al ( , 2000Ibáñez et al ( , 2003, Saccorotti et al (2001), Martinez-Arevalo et al (2003), Benitez et al (2007), Carmona et al (2010Carmona et al ( , 2012Carmona et al ( , 2014, and García-Yeguas et al (2010). One of the objectives of these seismic studies is to provide 2D or 3D structure of the area, by using active or passive data as has been done by Ben-Zvi et al (2009), Zandomeneghi et al (2009), and Prudencio et al (2013).…”
Section: Introductionmentioning
confidence: 92%
“…These swarms contained small earthquakes, with magnitudes of below 3. They occurred mostly along fracture systems trending NE–SW (Vila et al 1992; Ibáñez et al 2003a), but with a variety of source mechanisms reflecting a complex relationship with subsurface magma motions (Ibáñez et al 2003b; Carmona et al 2010).…”
Section: The Sitementioning
confidence: 99%
“…Another clue that may help us with the interpretation of the differences between models F1 and F2 comes from the work of Carmona et al (2010). They investigated the geometry of the fault planes involved in the 1999 seismic series of Deception Island volcano (Ibáñez et al 2003a) located under the northern half of Port Foster.…”
mentioning
confidence: 99%
“…In reference to the array analysis from Blanco et al (2015), the information provided is vague and inconsistent, because some of the most important data to be given are the geometries and resolutions of the seismic antennas Almendros et al 1999;Almendros et al 2000;Ibáñez et al 2000;Saccorotti et al 2001;Almendros et al 2004;Carmona et al 2010). Depending on its geometry, an array will have preferential directions of resolution, and in Blanco et al (2015), this information is missing, and therefore, we cannot determine whether the absence of information is due to the absence of signals or to limitations in the resolution of the instruments.…”
Section: Seismological and Geodetic Datamentioning
confidence: 92%